The suitcase six attempts to cross a border - Saunders, Frances Stonor 1966- (Jonathan Cape, 2021)
Ten years ago, Frances Stonor Saunders was handed an old suitcase filled with her father's papers. 'If you open that suitcase you'll never close it again,' warned her mother. Her father's life had been a study in borders -- exiled from Romania during the war, to Turkey then Egypt and eventually Britain, and ultimately to the borderless territory of Alzheimer's. The unopened suitcase seems to represent everything that had made her father unknowable to her in life. Now she finds herself with the dilemma of two competing urges: wanting to know what's in the suitcase, and wanting not to know. So begins this captivating exploration of history, memory and geography, as Frances Stonor Saunders unpicks her father's and his family's past. Is it possible to bring her father back, to summon once more someone who was distant and elusive when alive? The past is always the history of loss, of black holes, of things gone missing. The Suitcase is an extraordinary, heroic effort of retrieval, driven by the ache for completion. It is about the silences and stories that protect us, and the borders we construct, literally and figuratively, to fortify our sense of who we are
Keywords: Geschichte 1931-1995; Familie; Auswanderung; Rumänien; Saunders, Frances Stonor; Saunders, Frances Stonor / Family; Romanians / Biography; Immigrants / Biography; Exiles / Biography; Fathers and daughters / Great Britain; Exiles; Families; Fathers and daughters; Immigrants; Romanians; Great Britain; Autobiographies; Biographies; Family histories; Biografie